Mengembangkan Pemahaman Literasi Budaya dan Kewargaan Pada Anak Sekolah Dasar di Era Globalisasi - Widianti Nurohmah; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Abstract. In an increasingly advanced era of globalization, it is important for people to have a strong understanding of various cultures and nationalities. Primary school is an ideal place to build this understanding early on. Cultural and civic literacy refers to a person's ability to act as part of a culture and nation in their social environment. The method used in this research is a descriptive qualitative method based on literature study. It is hoped that the literature studies obtained by students can develop an understanding of cultural and civic literacy through activities and learning approaches.